Working with families : guidelines and techniques - Edwards, John T. (Hoboken, N.J. : John Wiley & Sons, 2011)
'Many helping professionals have had little to no formal training working with families. This book is a clinical guide for any type of family work, from one-time contact with families in a medical setting to intensive in-home family work. It takes a systems-oriented, problem-solving approach to counseling, emphasizing results rather than exploration. Filled with field-tested techniques, clinical suggestions, and client exercises, as well as alerts to potential pitfalls and how to avoid them, the book is ideal for therapists, substance abuse counselors, and school counselors'--
Includes bibliographical references and index.
Keywords: Family psychotherapy; Counseling; Marital psychotherapy